Representasi Unsur Budaya Masyarakat Jawa Tengah dalam Novel Sang Maha Sentana Karya Filiananur : Kajian Antropologi Sastra - Ica Melvira Pratiwi; Joko Purwanto; Nurul Setyorini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the representation of cultural elements of Central Javanes society in Filiananur’s novel Sang Maha Sentana : A Study of Literary Anthropology. This study is a descriptive qualitative study, the focus of this study is the representation of cultursl elements of Central Javanese society in Filiananur’s novel Sang Maha Sentana. Data collection techniques are carried out using interactive analysis techniques. Data analysis is carried out using interactive analysis techniques. Data presentation techniques are carried out using informal techniques. The data source in this paper is Filiananur’s novel Sang Maha Sentana. From the results of the study, it is concluded that the representation of cultural elements of Central Javanese society in the novel Sang Maha Sentana consists of: (a) language systems in the form of Javanese, literary language, and Dutch; (b)the knowledge system is divided into three, namely knowledge of natural flora, knowledge of substances, raw materials and objects araind them, knowledge of the nature and behavior of fellow human beings is divided into three subsystems, namely matchmaking customs, marriage customes, norm systems, knowledge of space and time; (c) the system of equipment and life technology is divided into six, namely weapons, containers, food, clothing, shelter, and transportation; (d) livelihood systems;(e)religious systems; (f) art.